CURRICULUM INTEGRATION; A STRATEGY FOR BETTER PATIENT CARE - Tanzeela Khalid (Journal of University Medical & Dental College, 2020)
Better patient care is the ultimate goal of any undergraduate medical education program. There is an ever increasing gap between public expectations and undergraduate medical education in our country. Growing awareness about patient rights has led to explicit public demands for a safe doctor who is accountable not only for his competence but also professionalism and good communication skills as well. On the other hand the traditional, discipline based curriculum being followed in majority of our medical colleges does not appear to be congruent with such societal needs. The end result is a product that fails to satisfy its consumer and faculty burn out.